Diagenesis of a SE Asian Cenozoic carbonate platform margin and its adjacent basinal deposits - Wilson, Moyra (Elsevier Science BV, 2013)
This study provides insights into the diagenesis of a SE Asian Tertiary carbonate platform and the variations inalteration that occur across platform top, margin, slope and adjacent basinal deposits. A petrographic,cathodoluminescent and stable isotopic study allowed evaluation of the diagenesis of the Kedango Limestoneof Borneo. The Kedango Carbonate Platform developed as a predominantly low to moderate energy system inthe semi-enclosed marine embayment of the Kutai Basin during the Eocene to Miocene. Early alterationthrough pervasive micritisation and minor isopachous fringing, syntaxial overgrowth and bladed to radiaxialcements was due to marine diagenesis on the basis of limited, relatively enriched stable-isotope compositionsand non-luminescent cathodoluminescent (CL) characters. Minor early marine cementation formedjust in the shallowest-platform top and margin deposits, and was likely promoted in high energy portionsof the platform due to wave and/or current activity. Dissolution cavities, banded calcite cements with variableCL characteristics and depleted stable-isotope compositions, micritic sediment infiltration and alveolar texturesare minor features, but together are indicative of localised subaerial emergence and meteoric diagenesis.The most prevalent and pervasive diagenetic feature of the deposits is the neomorphic alteration andreplacement of metastable bioclasts and micritic matrix, together with contiguous calcitisation of pore spaces.Burial fluidswith amarine character are inferred as the parent diagenetic fluid, since stable-isotope compositionsfor the neomorphic spar is largely consistent with precipitation from SE Asian Oligocene–Miocene seawater in aburial environment. Tectonic subsidence, the protected semi-enclosed marine embayment setting, and probablyterrestrial runoff, together with component variability reflecting local environmental variations, are inferred tohave been major controlling influences on the diagenesis of the Kedango Platform. Variations in diagenesis acrossbathyal, slope and shallow-platform deposits of the Kedango Limestone are not as marked as in other platformsfrom the region.